ANALISIS ANGGARAN DAN REALISASI BIAYA PRODUKSI KELAPA SAWIT (STUDI KASUS PADA PT PERKEBUNAN NUSANTARA XIII (PERSERO) PONTIANAK) - B51112031, Meniati Saragih (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This study aims to determine how to use the budget as a tool of production planning and control production costs at PT. Perkebunan Nusantara XIII (Persero). This research is expected to be input for the company's management regarding the role of the budget as a planning and control tool. In this paper the author will compare the budget and the realization that had been developed by the company's actual production costs of the production budget in achieving the optimal goal. In this study using the case study method using descriptive analytical approach, which collects data and sufficient information, which can provide a clear picture of an object of research which will then be processed, analyzed and summarized. The results showed that the profit in 2013 experiencing decreased dramatically when compared to the profit in 2012 and increased again in 2014. The use of the production costs of the year 2012, 2013 and 2014 PTPN XIII (Persero) is not well controlled. His lack of control over many aspects, one of which is the use of the cost of production so that in the year 2013 income declined drastically and after an evaluation, a very good then profits can be increased in the year 2014. To avoid deviations - deviations are not desirable, the cost of palm oil production in PTPN XIII can be controlled and in its implementation should be monitored carefully to what has been budgeted to be realized properly so as to provide income that thrive from year to year. Keywords: Budget, Cost of Production